Artificial Nutrition and Hydration in People With Late-Stage Dementia. (June 2017) - Smith, Lenora; Ferguson, Rita
Abstract : The progressive nature of dementia marks this disease as a terminal illness in the advanced stage, and palliative care rather than curative treatment is indicated. The use of feeding tubes to deliver artificial nutrition and hydration at end of life is often part of the plan of care for people with dementia. Current evidence, however, suggests that tube feeding in advanced dementia is not beneficial and the burdens of the procedure and the feedings themselves outweigh any benefits. Evidence also reveals that healthcare providers may lack evidence-based knowledge about artificial nutrition and hydration to adequately inform families and surrogate decision makers. This article examines the evidence regarding use of artificial nutrition and hydration for patients with end-stage dementia and offers implications for home care clinicians.